Hypoxic cardiorespiratory reflexes in the facultative air-breathing fish jeju (Hoplerythrinus unitaeniatus): role of branchial O-2 chemoreceptors - Lopes, Jane Mello; Boijink, Cheila de Lima; Florindo, Luiz Henrique [UNESP]; Costa Leite, Cleo Alcantara; Kalinin, Ana Lucia; Milsom, William K.; Rantin, Francisco Tadeu (Springer Heidelberg, 2010)
In one series of experiments, heart frequency (f (H)), blood pressure (P (a)), gill ventilation frequency (f (R) ), ventilation amplitude (V (AMP)) and total gill ventilation (V (TOT)) were measured in intact jeju (Hoplerythrinus unitaeniatus) and jeju with progressive denervation of the branchial branches of cranial nerves IX (glossopharyngeal) and X (vagus) without access to air. When these fish were submitted to graded hypoxia (water PO2 similar to 140, normoxia to 17 mmHg, severe hypoxia), they increased f (R) , V (AMP), V (TOT) and P (a) and decreased f (H). In a second series of experiments, air-breathing frequency (f (RA)), measured in fish with access to the surface, increased with graded hypoxia. In both series, bilateral denervation of all gill arches eliminated the responses to graded hypoxia. Based on the effects of internal (caudal vein, 150 mu g NaCN in 0.2 mL saline) and external (buccal) injections of NaCN (500 mu g NaCN in 1.0 mL water) on f (R) , V (AMP), V (TOT), P (a) and f (H) we conclude that the O-2 receptors involved in eliciting changes in gill ventilation and associated cardiovascular responses are present on all gill arches and monitor the O-2 levels of both inspired water and blood perfusing the gills. We also conclude that air breathing arises solely from stimulation of branchial chemoreceptors and support the hypothesis that internal hypoxaemia is the primary drive to air breathing.
Keywords: Cardiorespiratory control; Hypoxia; O-2 chemoreceptors; Gills; Air breathing; Jeju; Hoplerythrinus unitaeniatus